Infrastructure 2 Pedestrian System Implementation: Costs and Profits Estimation - Pawel SKOKOWSKI; Krzysztof MAŚLANKA (Communications of International Proceedings, 2021)
This paper estimates costs and profits for an Infrastructure 2 Pedestrian (I2P) system implementation to increase human life and health safety. After the introduction, the I2P concept is discussed. Next, the expected cost of a single I2P device implementation is estimated. The potential savings for the I2P solution's different efficiency are also calculated. Economic factors supporting the need to develop this type of solution are presented for Poland and its capital city. Conclusions summarize the article.
Keywords: Pedestrian safety; infrastructure to pedestrian (I2P); accidents; costs; profits.